Improving the Smart Village Cluster With a New Smart Government Model - Antoni; Solly Aryza, (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
The development of Electronic Government (e-Gov) is an effort to develop electronic-based governance in order to improve the quality of public services. e-Gov is the process of utilizing information technology as a tool to help run the government system more efficiently. Realizing the huge benefits of e-Gov, the Indonesian government has issued a National Policy and Strategy for e-Gov Development through Presidential Instruction Number 3 of 2003 as a legal umbrella for all policies in the field of e-Gov as well as several articles in Law Number 6 of 2014 concerning Villages that explicitly talk about Information Communication Technology (ICT) for Villages. The Open Group Architecture Framework (TOGAF) is one of the methods that can be used in planning and designing e-Gov. The purpose of this study is to build an e-Gov model, especially services, and develop an e-Gov implementation strategy for Village Government in Pari City, Pantai Cermin District, Serdang Bedagai Regency towards Smart Village. Based on the value chain of the Pari City Village Government, the e-Gov model built has implications for the Pari City Village Government e-Village model consisting of Village Administration Service Applications, Village Financial Governance Applications, Village Development Planning Applications, and Land Ownership Document Data Management Applications. The implementation of the e-Government model is carried out in stages starting from the procurement of better facilities, equitable distribution of communication networks, and increasing better human resources (village apparatus), then the e-Government model that has been built will be applied.